Intra-Orbital Lesions (Melanoma/Retinoblastoma) Radiological Findings Correlation on Ultrasound and MRI - Sana Sharif, Mahwash Shoaib, Maham Khalid, Afshan Shiekh, Muhammad Nauman Akram, Asma Afzal Kiani, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The purpose of this study is to determine intra-orbital lesions by radiological findings correlation on ultrasound and MRI. Study Design: Prospective study Place and Duration: Radiology department of Sindh Govt Hospital Liaquatabad, Karachi and Jinnah hospital, Lahore for the duration from May 2021 to April 2022. Methods: There were 75 patients of both genders presented in this study. Included patients were aged between 2-50 years. A CT scan was performed on all patients with a clinical suspicion of ocular and orbital abnormalities referred from the ophthalmology department. Outcomes among all patients were determined in terms of radiological findings correlated with MRI and ultrasound. SPSS 22.0 was used to analyze complete data. Results: Among 75 cases, there were 43 (57.3%) males and 27 (42.7%) were males. Mean age of the patients was 21.8±4.42 years. Majority of the cases 70 (93.3%) were non traumatic and 5 (6.7%) cases were traumatic. Among 70 cases of non-traumatic lesions, the most common disease was neoplasm found in 32 (45.7%) cases, followed by infective and inflammatory lesions in 22 (31.4%) cases. We found that retinoblastoma was the most common non-traumatic lesion in 21 (30%) cases followed by endocrine orbitopathy and orbital cellulitis. Among 5 cases of traumatic lesions, frequency of fractures were 4 (80%), preseptal soft tissue swelling was found in 3 (60%) cases and retained foreign body (orbital and lid) in 2 (40%) cases. Conclusion: CT is used to diagnose lesions, plan surgery, and track patients with ocular and orbital diseases. MDCT is superior for bone assessment, calcification detection, and determining lesion site, extent, and configuration. MDCT is suitable for evaluating ocular and orbital lesions. Keywords: CT, Ultrasound, MRI, Orbital lesions, Ocular lesions